Studies on chemical constituents and biological activities of Nauclea Officinalis and Nauclea Subdita / Liew Sook Yee - Liew, Sook Yee (2014)
The phytochemical studies on two species of Rubiaceae; Nauclea officinalis and Nauclea subdita have been carried out. Twenty one compounds were successfully isolated and purified using several chromatography techniques such as column chromatography (CC), thin layer chromatography (TLC), preparative thin layer chromatography (PTLC), and high performance liquid chromatography (HPLC). The compounds are naucline, nauclefine, naucletine, angustine, angustoline, 3,14-dihydroangustoline, angustidine, subditine, strictosamide, pumiloside, naucleficine, naucleactonin C, harmane, 1,2,3,4-tetrahydro-1-oxo-β-carboline, benzamide, cinnamide, blumenol B, blumenol A, β-sitosterol, stigmast-4-en-3-one and vanillin. Naucline and subditine are new indole alkaloids which were isolated from the bark of Nauclea officinalis and Nauclea subdita respectively. The structure of the isolated compounds were elucidated using various spectroscopic methods; 1D-NMR (1H, 13C, DEPT), 2DNMR (COSY, HSQC, HMBC, NOESY), UV, mass spectrometry and comparison with literature reviews. Among five compounds, subditine exhibited good cytotoxic activity against human prostate cancer cells which are LNCaP and PC-3 with IC50 of 12.24 ± 0.19 μM and IC50 of 13.97 ± 0.32 μM respectively. IC50 values of angustoline, angustidine, angustine and nauclefine were in the range of 58.09-149.16 μM. Subditine showed higher selectivity against LNCaP and PC-3 prostate cancer cells than the normal prostate cells; RWPE-1 (selectivity index: [LNCaP/PC-3] = 2.49/2/18). In addition, ten alkaloids was tested for anticholinesterase activity. Only angustidine showed potent inhibition with IC50 of 6.54 ± 0.37 μM on acetylcholinesterase enzyme (AChE). On the other hand, for butyrylcholinesterae enzyme (BChE), three alkaloids exhibited potent inhibition; angustidine, angustine and nauclefine with IC50 of 0.31 ± 0.07 μM, 1.56 ± 0.05 μM and 2.21 ± 0.03 μM, respectively. Angustidine was the most potent inhibitor of BChE than the standard galanthamine. Enzyme kinetic studies and molecular docking suggested that the most potent compound, angustidine possess mixed inhibition mode with inhibition constant, Ki value of 6.12 μM and its binding site was strongest at the bottom gorge of hBChE and formed hydrogen bonding with Ser 198 and His 438.